BIOGRAFI INTELEKTUAL MUHADDITS NUSANTARA ABAD XX: HABIB SALIM BIN JINDAN - Karyadi, Fathurrochman (Nabawi: Journal of Hadith Studies, 2021)
Not many muhaddits (hadith experts) were found from the archipelago Nusantara. The name Habib Salim bin Jindan (1906-1969) is one of the figures. There are more than 50 of his works in the field of hadith and volumes including al-'Uqud al-Dirayah fi al-Musalsalat al-Fakhriyah in three volumes, Tanqih al-Akhbar fi al-Nasikh wa al-Mansukh min al-Akhbar, and al-Mawahib al-'Alawiyah fi al-Arba'in al-Nabawiyah. Some sanads mention Habib Salim's name as a narrator of hadith. It is no wonder that there are no less than 400 teachers from various countries. This paper will reveal Habib's intellectual biography as well as state his position as a hadith expert in Indonesia.